Analisis Perbandingan Pegawai Tetap dan Pegawai Kontrak Ditinjau dari Produktivitas dan Kompetensi Kerja pada Kantor Camat Raba Kota Bima - Maharani, Ulfa; Badar, Muhammad (LANCAH: Jurnal Inovasi dan Tren, 2023)
This research aims to determine and analyze the comparison of permanent employees and contract employees in terms of productivity and work competency at the Raba sub-district office, Bima City. This research is of a comparative type with a Likert scale questionnaire as the research instrument. The population used in this research were all employees at the Raba Subdistrict Office, 60 respondents, consisting of 30 permanent employees and 30 contract employees. The sample in this study was all permanent employees and contract employees at the Raba Subdistrict Office, so the sample totaled 60 respondents. The sampling technique used in this research is a saturated sampling technique. The data in this research was collected using observation techniques, questionnaires and literature study. Data analysis techniques use validity tests, reliability tests and difference tests. The research results show that there are significant differences between permanent employees and contract employees when viewed from work productivity and work competency at the Raba District Head